A systematic review and meta-analysis of acupuncture in aspiration caused by post-stroke dysphagia - Li, Hongwei; Li, Jie; Wang, Xu; Zhang, Zhilong (Frontiers in Neurology, 2024)
Objective This systematic review and meta-analysis aims to systematically evaluate the effectiveness and safety of acupuncture in the treatment of aspiration caused by post-stroke dysphagia. Methods A computer search was conducted in nine databases, including the China National Knowledge Infrastructure (CNKI), China Science and Technology Journal (VIP), Wan-fang Database, China Biomedical Literature Database (CBM), PubMed, Web of Science, Cochrane Library, Embase, and Chinese Clinical Trial Registry (ChiCTR), from their inception until April 2024. Clinical randomized controlled trials comparing acupuncture combined therapy or single therapy with control interventions for the treatment of aspiration caused by post-stroke dysphagia were included. The primary outcome measure was the Penetration Aspiration Scale (PAS), and secondary outcome measures included the overall effective rate, video fluoroscopic swallowing study (VFSS), and hyoid bone displacement. The statistical analysis was performed using RevMan 5.3 and Stata 16.0. Results A total of 16 articles involving 1,284 patients were included. The meta-analysis results showed that acupuncture combined therapy or single therapy was more effective in improving PAS scores compared to conventional rehabilitation therapy or balloon dilation of the catheter [WMD = −1.05, 95% CI (−1.30, −0.80), Z = 0.82, p = 0.00 < 0.05]. It was also more effective in improving VFSS scores [WMD = 1.32, 95% CI (0.08, 2.55), Z = 2.09, p = 0.04 < 0.05] and hyoid bone displacement [WMD = 2.02, 95% CI (0.86, 3.18), Z = 3.41, p = 0.00 < 0.05]. Additionally, acupuncture had a higher overall effective rate [WMD = 1.21, 95% CI (1.14, 1.29), Z = 5.76, p = 0.00 < 0.05] and a lower incidence of adverse events. Sensitivity analysis indicated that the literature had minimal impact on the results, and bias tests showed no publication bias. Conclusion Acupuncture combined therapy and acupuncture single therapy can effectively improve aspiration caused by post-stroke dysphagia with a low incidence of adverse events. However, due to the low quality of the included literature, more high-quality randomized controlled trials are still needed to confirm the effectiveness and safety of acupuncture in the treatment of aspiration caused by post-stroke dysphagia. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023462707, identifier CRD42023462707